Effects of Plate Velocity Slowdown on Altering Continental Collision Patterns and Crustal-Lithospheric Deformation During the Collision Process - Liu, Mengxue; Yang, Dinghui; Huangfu, Pengpeng (Frontiers in Earth Science, 2022)
Continental collision zones are widely distributed across the earth’s surface with diverse types of tectonic processes. Even the same collision zone shows significant lateral tectonic variations along its strike. In this study, we systematically investigated how plate velocity slowdown after the closure of the ocean influences the continental collision evolution, as well as the effects of kinematic characteristics and continental rheology on varying the continental collision modes in a plate velocity slowdown model. From the comparison between the constant plate velocity system (CVS) and the plate velocity-dropping system (VDS), we can conclude the following: Plate velocity dropping promotes the extension inside the slab by decreasing the movement of the surface plate, whereas slab pull increases as subduction continues. The timing of the subducting slab break-off and the polarity alteration was initiated earlier in the plate velocity drop models than in the constant plate velocity models, and fast convergence may have triggered multiple episodes of slab break-off and caused strong deformation adjacent to the collision zone. Parametric tests of the initial subducting angle, plate convergence velocity, and continental crustal rheological strength in VDS indicated the following: (1) Three end members of the continental lithospheric mantle deformation modes were identified from the VDS; (2) models with a low subducting angle, fast continental convergence velocity, and medium-strength overriding crust were more likely to evolve into a polarity reversed mode, whereas steep-subducting-angle, slow-plate-velocity, weak-overriding-crust models tended toward a two-sided mode; (3) a strong overriding continent is more liable to develop a stable mode; and (4) overriding crustal rheological strength plays a significant role in controlling changes in continental collision modes.